Eco Labeling – Business or Corporate Social Responsibility (CSR) for major consumer electronics companies - Ong, Tee Guan / Mr (2010)
In spite of the positive effect in environmental protection using such Eco labels, there are critics if the environmental benefit gained from the labeling program really exceeds the social cost associated with its implementation. The major source of the cost could be industries’ additional cost burden to comply with the Eco Labeling requirements (e.g. investment to change product design, manufacturing process, input materials and technologies, compliance verification cost for testing and auditing, license fees to use the ecolabel, etc). Especially for international trade, the manufacturers who try to show their product’ environmental qualities by means of Eco labels in more than one foreign markets can not but bear redundant cost, because each national Eco labeling program has independent, separate and not-harmonized requirements, processes and fee structures. Companies will have to select the most suitable Eco labeling program based on the societal expectations. Major consumer electronics companies (e.g. Toshiba, Sony, Samsung…etc) are riding on Eco labeling trend to promote their brand and product sales. Their motives to take on Eco labeling scheme maybe due to improving their business, or just being socially responsible, or both. In this paper, we shall explore the reason(s) behind the drives of Eco labeling for some of the major consumer electronics companies